Sensorial and chemical changes in honey roasted peanuts and roasted peanuts stored under different temperatures - Nepote, Valeria (2006)
The purpose of this work was to determine the oxidative stability in honey roasted peanuts (HRP) and roasted peanuts (RP). Chemical analysis and descriptive analysis were performed on samples of HRP and RP stored at −15, 23 and 40 °C. The chemical analyses, peroxide and thiobarbituric acid reactive substance (TBARS) values, and the descriptive analysis were performed during 126 days of storage to determine protective effect of honey coating on the product stability. Peroxide and TBARS values, oxidized and cardboard flavors increased and roasted peanutty flavor decreased across the storage time for both products. Addition of honey coating provided protection against lipid oxidation. Peroxide value reached 10 meqO2 kg−1 after 6 days in RP and 36 days in HRP at 23 °C.